2017
DOI: 10.1111/jmi.12608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of donor and acceptor's fluorescence lifetimes on the method of applying Förster resonance energy transfer in STED microscopy

Abstract: SummaryFörster resonance energy transfer (FRET) probes being used to improve the resolution of stimulated emission depletion (STED) microscopy are numerically discussed. Besides the FRET efficiency and the excitation intensity, the fluorescence lifetimes of donor and acceptor are found to be another key parameter for the resolution enhancement. Using samples of FRET pairs with shorter donor lifetime and longer acceptor lifetime enhances the nonlinearity of the donor fluorescence, which leads to an increased re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Combination with other readouts (such as force, electrophysiology or mass spectrometry) enhances the information content of imaging experiments, and it will be interesting to develop such hybrid approaches to be more accessible for biology-driven applications. Furthermore, combining SRM with fluorescence spectroscopy techniques such as fluorescence recovery after photobleaching (FRAP) 130,131 , Förster resonance energy transfer (FRET) 132,133 , and FCS 134 will further expand its applications to the study of structural dynamics and molecular interactions in living cells.…”
Section: Srm As a Tool To Inform Biologymentioning
confidence: 99%
“…Combination with other readouts (such as force, electrophysiology or mass spectrometry) enhances the information content of imaging experiments, and it will be interesting to develop such hybrid approaches to be more accessible for biology-driven applications. Furthermore, combining SRM with fluorescence spectroscopy techniques such as fluorescence recovery after photobleaching (FRAP) 130,131 , Förster resonance energy transfer (FRET) 132,133 , and FCS 134 will further expand its applications to the study of structural dynamics and molecular interactions in living cells.…”
Section: Srm As a Tool To Inform Biologymentioning
confidence: 99%
“…Later, this principle was successfully applied for improving the resolution of STED microscopy 2-3-fold. In this approach, named FRET-assisted STED (FASTED) excited acceptors are depleted in the outer rim of the excitation spot leading to donor de-excitation and improved spatial resolution for the aforementioned principles [155,156].…”
Section: Don't Dos In Fretmentioning
confidence: 99%
“…Recent technological developments using dark acceptor FRET couples (consisting of a fluorescent Donor and an absorbing but non-emitting or "dark" Acceptor) and fast FLIM imaging allow such multiplexing and an intensity-independent read-out of FRET efficiency [10]. Furthermore, super-resolution optical microscopy such as STED takes benefit of such probes by a resolution increase to nm scale due to non-linear effects [11]. So far, however, no reported applications in the field of platelet research can be found.…”
Section: Labeled Platelets Isolated From Transgenic Mice Expressing a Fluorescent Markermentioning
confidence: 99%